2023
DOI: 10.1097/md.0000000000032871
|View full text |Cite
|
Sign up to set email alerts
|

Primary acinic cell carcinoma of the trachea: A case report and literature review

Abstract: Rationale: Salivary gland-type acinic cell carcinoma (ACC) is a low-grade malignancy. Primary ACC of the trachea and lungs is rare; here, we describe 1 such case. The histological morphology of tracheal ACC was similar to that of its salivary gland-associated equivalent. Because of its rarity, it is easily misdiagnosed as another type of tracheal or lung tumor. Microscopic analysis of pathological features and immunohistochemistry help diagnose primary ACC of the trachea and lungs. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 25 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…18 Four cases of AciCC were reported to be combined with carcinoid tumour 178,[180][181][182] ; all showed neuroendocrine marker staining including in the AciCC component, 178,[180][181][182] in contrast to lack of expression of neuroendocrine markers in pure AciCCs of the lung. [16][17][18][19]47,[159][160][161]165,166,179 Pulmonary AciCC tends to behave less aggressively than other pulmonary carcinomas. A review of 25 pulmonary AciCC with up to 8 years of follow-up found no deaths, one recurrence, and two cases of lymph node metastasis.…”
Section: Hyalinizing Clear Cell Carcinomamentioning
confidence: 99%
See 4 more Smart Citations
“…18 Four cases of AciCC were reported to be combined with carcinoid tumour 178,[180][181][182] ; all showed neuroendocrine marker staining including in the AciCC component, 178,[180][181][182] in contrast to lack of expression of neuroendocrine markers in pure AciCCs of the lung. [16][17][18][19]47,[159][160][161]165,166,179 Pulmonary AciCC tends to behave less aggressively than other pulmonary carcinomas. A review of 25 pulmonary AciCC with up to 8 years of follow-up found no deaths, one recurrence, and two cases of lymph node metastasis.…”
Section: Hyalinizing Clear Cell Carcinomamentioning
confidence: 99%
“…At least 32 cases of AciCC primary to the lung have been reported. [16][17][18][19] These tumours are usually associated with a bronchus or the trachea, although two cases were found deep in the pulmonary parenchyma. 159,160 Four cases were reported in paediatric patients, aged 4-12 years, 18,46,47 three of which were associated with a foreign body.…”
Section: Hyalinizing Clear Cell Carcinomamentioning
confidence: 99%
See 3 more Smart Citations